A Retrospective Evaluation of Pre-Pandemic Online Teacher Learning Experiences - Kufi, Elmaziye Ozgur (Sage Publications Inc, 2022)
Teachers are expected to encourage students to be active in the learning process in line with social-constructivist principles. However, when it comes to their own learning, they are obliged to attend activities organized by their institution. Triggered by this dilemma, this study introduced Computer-Mediated Communication as an alternative to the top-down delivery of trainer-fronted professional development and explored teachers' uptake of Web 2.0 in the pre-pandemic era. To obtain comprehensive insights into teachers' perceptions related to the use of Web 2.0 for their own learning, the study employed qualitative and quantitative methodology. Study results revealed that teacher development cannot be promoted with the use of Web 2.0 per se as it is very much dependent on teacher awareness, autonomy, beliefs, contextual realities but most significantly student learning. Despite limitations, this study highlights the principle of learner-centeredness as the key for promoting teacher development and the need to make prospective teacher learning practices an integral part of student-focused activity. Based on the results of the study, it is recommended that the multi-dimensional nature of teacher learning and contextual realities at multiple levels are considered in the design of post-pandemic teacher development schemes, significantly in institutions with low-autonomy cultures in order to turn top-down teacher development practices which teachers are used to into teacher initiated bottom-up learning processes.
Keywords: teacher professional development; professional learning; Web 2.0; computer mediated communication; virtual learning environments